Emulgel: A Recent Approach For Topical Drug Delivery System - Singh, R. P.; Parpani, S.; Narke, R.; Chavan, R. (Asian Journal of Pharmaceutical Research and Development, 2014)
Topical drug delivery system can be defined as direct effects of formulation or drug containing medication to the skin to get localizing effect of drug or directly cure cutaneous disorders. Emulgels has to be used as a topical drug delivery system for hydrophobic drugs. When gels and emulsions are used in combined form the dosage forms are referred as emulgels. Emulgels have emerged as one of the most interesting topical delivery system as it has dual release control system i.e. gel and emulsion. The major objective behind this formulation is delivery of hydrophobic drugs to systemic circulation via skin. In recent years, there has been great interest in the use of novel polymers which can function as emulsifiers and thickeners because the gelling capacity of these compounds allows the formulation of stable emulsions and creams by decreasing surface and interfacial tension and at the same time increasing the viscosity of the aqueous phase. In fact, the presence of a gelling agent in the water phase converts a classical emulsion into an emulgel. Emulgels for dermatological use have several favourable properties such as being thixotropic, greaseless, easily spreadable, easily removable, and emollient, no staining, water-soluble, longer shelf life, and bio-friendly, transparent & pleasing appearance. These emulgels are having major advantages on novel vesicular systems as well as on conventional systems in various aspects. Various permeation enhancers can potentiate the effect. So emulgel formulations can be used as better topical drug delivery systems over present conventional systems available in market.